PENERAPAN LIVING VALUE EDUCATION PROGRAM (LVEP) DALAM MEMBENTUK KARAKTER ANAK USIA DINI DI TK AISYIYAH 11 PALEMBANG - Mardiana Sari; Fitria Lufiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the implementation of the Living Value Education Program (LVEP) in shaping the character of early childhood at Aisyiyah 11 Kindergarten in Palembang. Character education is very important to be instilled from an early age because this period is the golden age of child development, both physically, cognitively, and emotionally. The phenomenon of moral degradation such as individualism, lack of tolerance, and aggressive behaviour in children shows the need for an effective approach in shaping character from an early age. LVEP, as a values education program developed with the support of UNESCO, emphasizes universal values such as honesty, responsibility, tolerance, and peace. This study employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that the implementation of LVEP at TK Aisyiyah 11 is carried out through various integrated learning activities that incorporate life values. Teachers use a play-based learning approach, storytelling, discussions, and reflective activities to install these values. Positive impacts are evident in changes in children's behaviour, becoming more cooperative, responsible, and showing empathy toward peers. However, there are challenges in implementing LVEP, such as a lack of understanding among parents and inconsistency in the values taught at home. Overall, the implementation of LVEP has proven effective in shaping the character of young children and is recommended as an alternative approach to character education in early childhood education settings.